POTENSI SITOTOKSIK DAN ANTIBAKTERI EKSTRAK DAUN Laportea interrupta (L.) Chew (JELATANG AYAM) TERHADAP Staphylococcus aureus - Okti Mindi Safitri; Nurhamidah Nurhamidah; Hermansyah Amir (ALOTROP, 2018)
This research aims to determine the profile of phytochemicals, determine the level of cytotoxic extract toward the larva of Artemia salina Leach by using Brine Shrimp Lethality Test (BSLT) method, and to measure how much the activity of  antibacteria leaf ekstract of Laportea Interrupta (L.) Chew  (Jelatang Ayam )  toward the Staphylococcus aureus bacteria. The leaf of L. interrupta  (L.) Chew are dried and grinded well. The half of grinded sample are tested by phytochemical  profile and another one are ekstracted by using etanol liquid for three days then they are evaporated. The result of fitokimia leaf L. interrupta  (L.) Chew test contains secondary metabolite alkaloid,  tanin, terpenoid,  and saponin. The result of cytotoxic extract of leaf L. interrupta  (L.) Chew toward the A. salina Leach is obtained LC50 for 93,33 ppm, so, the L. interrupta  (L.) Chew is toxic because it is in the range of 31 ppm to 1000 ppm and it can be potentially as a anticancer agents. The eksract of Jelatang Ayam leaf can obstruct the growth of S. aureus, on 5 x 104 clear zone concentration that formed 9 mm being medium categorized. The more concentration of the Jelatang leaf ekstract then more its obstruction energy.